2021
DOI: 10.3390/vaccines9040371
|View full text |Cite
|
Sign up to set email alerts
|

Intention to Get COVID-19 Vaccinations among Ophthalmology Residents in Poland: A Cross-Sectional Survey

Abstract: This study aimed to evaluate the acceptability of coronavirus disease of 2019 (COVID-19) vaccination among ophthalmology residents in Poland. An online, self-administered, anonymous survey was distributed among Polish ophthalmology residents in early 2021. Of 126 residents who completed the survey, 71.4% indicated that they would get vaccinated, 17.5% were unsure, and 11.1% would refuse vaccination. Married respondents with children (p = 0.036) and respondents living with their families (p = 0.310) were more l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 14 publications
0
23
0
Order By: Relevance
“…It should be noted, however, that one of the Polish studies [ 17 ] was partially interventional (an interview induced by information presented to the respondent on vaccination and COVID-19). Thus far, apart from the studies discussed above, most of the Polish studies on COVID-19 vaccine hesitancy have focused on selected professional [ 47 , 48 ] and societal groups [ 49 , 50 ]. Our study addresses the problem of vaccine hesitancy in the broadest way through multivariate statistical modeling, and primarily refers to the general population.…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted, however, that one of the Polish studies [ 17 ] was partially interventional (an interview induced by information presented to the respondent on vaccination and COVID-19). Thus far, apart from the studies discussed above, most of the Polish studies on COVID-19 vaccine hesitancy have focused on selected professional [ 47 , 48 ] and societal groups [ 49 , 50 ]. Our study addresses the problem of vaccine hesitancy in the broadest way through multivariate statistical modeling, and primarily refers to the general population.…”
Section: Discussionmentioning
confidence: 99%
“…Konopinska et al reported the results from an online survey of Polish ophthalmology residents in early 2021. 10 About 126 residents completed to survey; 71.4% indicated that they would get vaccinated, 17.5% were unsure about vaccination, and 11.1% said they would refuse vaccination. Residents with children and residents living with their families were more likely to accept vaccination in an effort to reduce infection in their families.…”
Section: Discussionmentioning
confidence: 99%
“…The response rate in the survey was not reported, and multivariable logistic regression for the willingness to take the COVID vaccine did not identify any statistically significant factors. 10 The factors analyzed included gender, marital status, living situation, size of the city, and treating COVID-19 patients. This study suggests that multiple factors influence individual decisions regarding vaccination even in healthcare workers who are potentially exposed to infected patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This increase might be related to a growing proportion of vaccinated persons and the resultant decrease in the level of COVID-19 fear. 29 The proportion of partly or fully vaccinated persons in Poland has increased substantially, from 5.8% at the beginning of the third wave (March 1, 2021) to 22.6% at the end of April 2021 and 36.1% on May 31, 2021. 30 Since May 9, 2021, all adults in Poland can register for the vaccination.…”
Section: Discussionmentioning
confidence: 99%